MODEL PEMBELAJARAN LAUFDIKTAT UNTUK MENINGKATKATKAN KETERAMPILAN MENULIS DALAM PEMBELAJARAN BAHASA JERMAN KELAS X SEMESTER 2 - Christondi, Fidelis; Wahyuningsih, Fahmi (LATERNE, 2020)
The ability to write in German is an important ability to recognize a vocabulary of the sentence.. The delivery of materials items in the school for class X second semester can apply the running dictation model. Running Dictation is suitable for beginners, in this case for students in Class X, second semester, to enrich the vocabulary and the students can write the appropriate noun. It is hoped that the ability of students to write will increase, so that the students can read, listen and speak better in German. Presented in the form of the concept idea that the writing ability for the class X second semester can be improved by using the running dictation. The article is based on basic ideas that 1) the learning model is a teaching innovationthe learning model is a teaching innovation, students will be excited and encouraged to participate in learning.. 2 the learning focus has mostly applied with music, film, and visual media, so that the use of a learning model in relation to psychomotor skills has made rare. 3) Theoretically, the walk dictation model for psychomotor skills, cognitive, and attention can attract attention so that students focus on learning. 4) the pupils in class X have difficulties with nouns in German. The method used is a literature study, the literature study is a search and research of literature by reading various books, magazines and other publications on research topics in order to create an article on a specific topic or an issue (Marzali, 2016:27). Data from reading sources such as books, journals, notes and others. The analysis technique used is content analysis. This article contains definitions, theories and journals on how to use the run dictation model to improve students' writing skills. Keywords: Laufdiktat, writing skills, learning model